Use of FreeStyle Libre Flash Monitor Register in the Netherlands (FLARE-NL1): Patient Experiences, Satisfaction, and Cost Analysis. (3rd November 2019) - Fokkert, M. J.; Damman, A.; van Dijk, P. R.; Edens, M. A.; Abbes, S.; Braakman, J.; Slingerland, R. J.; Dikkeschei, L. D.; Dille, J.; Bilo, H. J. G.
Abstract : In patients with diabetes mellitus (DM), adequate glucose control is of major importance. When treatment schemes become more complicated, proper self-management through intermittent self-measurement of blood glucose (SMBG), among others, becomes crucial in achieving this goal. In the last decade, continuous glucose monitoring (CGM) has been on the rise, providing not only intermittent information but also information on continuous glucose trends. The FreeStyle Libre (FSL) Flash CGM system is a CGM system mainly used for patients with DM and is designed based on the same techniques as early CGMs. Compared with earlier CGMs, the FSL is factory calibrated, has no automated readings or direct alarms, and is cheaper to use. Although less accurate compared with the gold standard for SMBG, users report high satisfaction because it is easy to use and can help users monitor glucose trends. The Flash Monitor Register in the Netherlands (FLARE-NL) study aims to assess the effects of FSL Flash CGM use in daily practice. The study has a before-after design, with each participant being his or her own control. Users will be followed for at least 1 year. The endpoints include changes in HbA1c, frequency and severity of hypoglycemias, and quality of life. In addition, the effects of its use on work absenteeism rate, diabetes-related hospital admission rate, and daily functioning (including sports performance) will be studied. Furthermore, cost-benefit analysis based on the combination of registered information within the health insurance data will be investigated. Ultimately, the data gathered in this study will help increase the knowledge and skills of the use of the Flash CGM in daily practice and assess the financial impact on the use of the Flash CGM within the Dutch healthcare system.